Gene Expression Profile of the Human Colorectal Carcinoma LoVo Cells Treated With Sporamin and Thapsigargin - Yang, Chun; Chen, Si-Jia; Chen, Bo-Wen; Zhang, Kai-Wen; Zhang, Jing-Jie; Xiao, Rong; Li, Peng-Gao (Frontiers in Oncology, 2021)
Sporamin, a proteinase inhibitor isolated from the sweet potato (Ipomoea batatas), has shown promising anticancer effect against colorectal cancer in vitro and in vivo but its mechanisms of action is poorly understood. In the present study, the high throughput RNA sequencing (RNA-seq) technology was applied to explore the transcriptomic changes induced by sporamin in the presence of thapsigargin (TG), a non-12-O-tetradecanolphorbol-13-acetate type cancer promoter, in the LoVo human colorectal cancer cells. Cellular total RNA was extracted from the cells after they were treated with vehicle (CTL), 1 μM of thapsigargin (TG), or 1 μM of TG plus 30 μM of sporamin (TGSP) for 24 h. The gene expression profiles of the cells were determined by RNA-seq on an Illumina platform. GO enrichment analysis, KEGG pathway analysis, protein-protein interaction (PPI) network construction, and transcription factors (TF) prediction were all performed based on the differentially expressed genes (DEGs) across groups with a series of bioinformatics tools. Finally, the effect and potential molecular targets of the sporamin at the transcriptome level were evaluated.The endoplasmic reticulum stress (ERS) response was the main cellular event induced by TG that was partially diminished by sporamin treatment. Among the 17915 genes detected in all samples, 46 DEGs were attributable to the effect of sporamin. Importantly, the expression of RGPD2, SULT1A3, and BIVM-ERCC5 were up-regulated but NYP4R, FOXN1, PAK6, and CEACAM20 were down-regulated. Sporamin enhanced the mineral absorption pathway, worm longevity regulating pathway, and pyrimidine metabolism pathway. Two TFs (SMIM11A and ATOH8) were down-regulated by sporamin. HMOX1 (up-regulated) and NME1-NME2 (down-regulated) were the main nodes in a PPI network consist of 16 DEGs that were modulated by sporamin in the presence of TG.Sporamin could favorably alter the gene expression profile of cancer cells, up-regulating the genes that contribute to the homeostasis of intracellular metal ions, the activities of essential enzymes and DNA damage repairment and finally contribute to the prevention and treatment of cancer. More studies are warranted to verify its effect on specific genes and delineate the mechanism of action implicated in the process.